On the Optimal Recovery of Integrals of Set-Valued Functions - Babenko, V.F.; Babenko, V.V.; Polishchuk, M.V. (Український математичний журнал, 2015)
We consider the problem of optimization of the approximate integration of set-valued functions from the class specified by a given majorant of their moduli of continuity performed by using the values of these functions at n fixed or free points of their domain. Розглядається задача оптимізації наближеного інтегрування на класах багатозначних функцій, що мають задану мажоранту модуля неперервності. При цьому використовуються значення функцій в n фіксованих або довільних точках області визначення.